2013
DOI: 10.1371/journal.pone.0066538
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Small Intestine Grafts Decellularization Methods for Corneal Tissue Engineering

Abstract: Advances in the development of cornea substitutes by tissue engineering techniques have focused on the use of decellularized tissue scaffolds. In this work, we evaluated different chemical and physical decellularization methods on small intestine tissues to determine the most appropriate decellularization protocols for corneal applications. Our results revealed that the most efficient decellularization agents were the SDS and triton X-100 detergents, which were able to efficiently remove most cell nuclei and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
85
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 42 publications
(50 reference statements)
7
85
0
2
Order By: Relevance
“…Tissue sections 5-lm thick were obtained with a microtome. To determine the effectiveness of cell removal (decellularization efficiency), the number of remaining nuclei in control and decellularized corneas was quantified by using 4,6-diamidino-2-phenylindole (DAPI) staining (Sigma-Aldrich) on deparaffinized tissue sections, 13 and the percentage of cell removal was determined for DPC samples. The number of remaining nuclear debris was determined per field.…”
Section: Histology Evaluation and Image Processing Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Tissue sections 5-lm thick were obtained with a microtome. To determine the effectiveness of cell removal (decellularization efficiency), the number of remaining nuclei in control and decellularized corneas was quantified by using 4,6-diamidino-2-phenylindole (DAPI) staining (Sigma-Aldrich) on deparaffinized tissue sections, 13 and the percentage of cell removal was determined for DPC samples. The number of remaining nuclear debris was determined per field.…”
Section: Histology Evaluation and Image Processing Analysismentioning
confidence: 99%
“…For quantitative analysis of the ECM, histochemistry was carried out to detect the main fibrillar and nonfibrillar ECM components on tissue sections as previously described by Oliveira et al 13 (all reagents were purchased to Sigma-Aldrich):…”
Section: Histology Evaluation and Image Processing Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, small tissue fragments were obtained, washed twice with phosphate‐buffered saline and stained with the LIVE/DEAD assay reagents (calcein/AM and ethidium homodimer‐1; Invitrogen, Carlsbad, CA, USA) following the protocols provided by Invitrogen. The number of alive and dead cells was determined by using a fluorescence microscope, and automatically quantified using ImageJ software as previous reported . Average and standard deviation values were obtained for 7‐ and 14‐days bioengineered samples.…”
Section: Methodsmentioning
confidence: 99%
“…82 The use of intestinal scaffolds has been extensively evaluated owing to cytokines and growth factors, such as FGF and TGF-β, 83 that are preserved after decellularization. 2(C,D)], and many studies have reported reconstruction of distinct organs, such as the cornea, 38 urethra, 84 vagina, 85 lung, 86 and heart, 87 using decellularized intestinal scaffolds. 2(C,D)], and many studies have reported reconstruction of distinct organs, such as the cornea, 38 urethra, 84 vagina, 85 lung, 86 and heart, 87 using decellularized intestinal scaffolds.…”
Section: Decellularized Intestinementioning
confidence: 99%